Formulation and Inhibitory Test of Feminine Cleansing Soap Combination of Young Areca Extract (Areca cathechu L.) and Manjakani Extract (Quercus infectoria) on the Growth of Candida Albicans - Ni Nyoman Wahyu Udayani; Ketut Agus Adrianta; I Gede Made Suradnyana; Ni Luh Putu Tris Yoga Cahyani (Gema Lingkungan Kesehatan, 2024)
One of the reproductive health problems that women often experience is vaginal discharge. About 85-95% vaginal discharge is caused by the fungus Candida albicans. To maintain the cleanliness of the female organ system, feminine cleansing soap is usually used. The use of traditional ingredients has smaller side effects and the price is also relatively affordable. Traditional ingredients that can be used are young areca nut (Areca catechu L.) and Manjakani (Quercus infectoria). Young areca nut seeds contain tannins, flavonoids, and saponins, while Manjakani fruit contains tannins and flavonoids which have anti-fungal activity. This study aims to determine the inhibitory power of feminine cleansing soap from areca nut extract (Areca cathechu L.) and Manjakani extract (Quercus infectoria) on the growth of Candida albicans. This research is a purely experimental laboratory which begins with the extraction process. 5 formulations of feminine cleansing soap were prepared, a combination of young areca nut extract (Areca cathechu L.) and Manjakani extract (Quercus infectoria) with a concentration percentage ratio of 5:10, 7.5:7.5, 10:5, 15:0 respectively and 0:15. The resulting preparations were tested for inhibition of the growth of Candida albicans. The results showed that a feminine cleansing soap combination of young areca nut extract (Areca cathechu L.) and Manjakani extract (Quercus infectoria) had an inhibitory effect on the growth of Candida albicans, namely F1, F2, F3, F4 and F5 which had average inhibition respectively of 21.33 ± 0.58 mm, 21.67 ± 0.58 mm, 22 ± 0 mm, 19.67 ± 1.53 mm. Thus, the findings show that all feminine cleansing soap formulations of a combination of young areca nut extract (Areca cathechu L.) and Manjakani fruit extract (Quercus infectoria) have an inhibitory effect on the growth of Candida albicans. Of the five formulations tested, the combination of extracts with a ratio of 0:15 (F5) showed the highest inhibition against Candida albicans with a mean inhibition zone diameter of 22.33 ± 0.58 mm.